Aplikasi Fitofarmaka Akupresur Menggunakan Aromaterapi Essential Oil Lemon untuk Mengatasi Dismenore pada Remaja: The Fitofarmaka Acupressure application using lemon essential oil aromatherapy to overcome dysmenorrhea in adolescents - Husnul Khotimah; Sri Utami Subagio (Faletehan Health Journal, 2021)
The treatment of dysmenorrhea mostly used pharmacological therapy but rarely applied phytopharmaceuticals such as acupressure and aromatherapy. The purpose of this study was to analyze the application of acupressure using lemon essential oil aromatherapy to treat dysmenorrhea pain in adolescents. The research type was quantitative and the research design was quasi experiment with non-equivalent control group design. The population of this study amounted to 185. The sampling technique used a non-probability sampling approach (saturated sampling). The sample size was determined by using calculations from Sastroasmoro & Ismael with a total sample of 52 people consisting of 26 in experimental group and 26 in control group. The data analysis used Wilcoxon signed rank test to examine the experimental and control group and Mann Whitney to compare them. The results of statistical analysis using Wilcoxon signed rank test for the experimental group (p=0.000) and the control group (p=0.000) showed that lemon oil essential therapy was effective in overcoming dysmenorrhea. The results of statistical analysis using Mann Whitney obtained p value 0.000 which is smaller than (p<0.05). It can be concluded that acupressure using aromatherapy is more effective in reducing dysmenorrhea than acupressure alone. The acupressure given made the respondents relaxed and their immunity increased, and the massages using aromatherapy that is inhaled to the lungs provides benefits both psychologically and physically.